Διερεύνηση των συμπτωμάτων κατάθλιψης σε φοιτητές πανεπιστημίου - Σωκράτους, Σωκράτης (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
BACKGROUND According to international literature, the frequency of occurrence of depressive symptoms among university students is high, approaching 71,2 percent in some studies. Additionally, research data suggest a strong association between depressive symptoms and socio-demographic characteristics of students and stressful life events. However, no relevant research has been conducted to date in Cyprus. The importance of this study stems from the possibility of the provision of evidence for a closer understanding concernig the factors associated with the presence of depressive symptoms (DS), and the launch possible psychopathology in Cypriot students. STUDY PURPOSE The aim of the present study was to investigate the intensity of depressive symptoms among undergraduate students population in Cyprus. In particular, the association between depressive symptoms among Cyrpiot undergraduate students population on one hand, and individual and social characteristics, selfreported health status, substance use / abuse, and stressful life events on the other was looked into. MATERIAL - METHODS A descriptive – correlational study design with cross-sectional comparisons was applied. Initially, descriptive statistics were used in the analysis of study variables. Frequency, mean values and standard deviations (SD) of continuous variables were reported. The depressive symptoms was assessed with the Center for Epidemiology Studies - Depression Scale (CES-D), while the number and severity of stressful life events with the LESS scale. The metric properties of these scales were determined with the use of Cronbach’s internal consistency coefficients. To assess between-group differences we used the chi-square test. The level of statistical significance was set at 0.005. Multivariate logistic regression models were pursued (calculation of odds ratios, plus 95 percent CIs) to determine the contribution of personal, family and academic characteristics of tudents and of their self-reported health status and drug use/abuse to the development of depressive symptoms. The same analysis was applied to elucidate the association between depressive symptoms and the number and intensity of stressful life events, after adjusting for confounders, such as sociodemographic characteristics. RESULTS The sample consisted of 1,500 students (29.9% male and 70.1% female). The mean age of participants was 20.34±2.08 years. Overall response rate was 85 percent. The prevalence of depressive symptoms [CES-D score ≥ 22] was 27.9 percent of the total sample. Strong correlations were found between depressive symptoms on one hand and health profile and academic, personal, and family characteristics of students on the other. In detail, students with a personal history (OR=1.88, 95% CI: 1.80 – 4.62), or a family history of a mental health disorder (OR=2.85, 95% CI: 1.77 – 4.60), students who reported poor/very poor physical (OR=1.45, 95% CI: 0.79 – 2.52), or mental health (OR=11.30, 95% CI: 7.05 – 18.08), smokers (OR=1.40, 95% CI: 1.00 – 1.89), and students with a drug addiction (OR=5.44, 95% CI: 2.95- 8.84), were more likely to manifest clinically significant depressive symptoms. Moreover, a higher likelihood of manifesting depressive symptoms was found in the following subgroups of students with learning difficulties (OR=1.85, 95% CI: 1.30 – 2.87), students who reported no or low level of satisfaction with their major or their courses (OR=1.95, 95% CI: 1.37 – 2.77), and students dissatisfied with the quality of the offered education (OR=1.66, 95% CI: 1.21 – 2.27), or of their living arrangement, social life and quality of available university facilities (OR=2.73, 95% CI: 2.00 – 3.72). Female students (OR=1.70, 95% CI: 1.17 – 2.33); students residing in rural or sub-rural areas (OR=1.60, 95% CI: 1.16-2.08); those with children (OR = 3.06 95% CI: 0.96 – 9.74), were again more likely to develop depressive symptoms (p <0.010 for all). Finally, higher scores on the LESS scale were associated with more frequent reports of depressive symptoms (x2 = 70.63, df = 4, p < 0.001). Logistic regression analysis with adjustment for socio-demographic characteristics confirmed that responders reporting the highest number of stressful life events during the previous year (N = 12 - 21, OR=2.64, 95% CI: 1.02 - 6.83) and the highest total score on the LESS scale (total score > 351, OR=3.03, 95% CI: 1.66 - 5.39) were more likely to manifest depressive symptoms. CONCLUSIONS The main finding of this study was that one in every three students experiences symptoms of depression, which is in accordance with international literature. Additionally, there were adintified vulnerable sub-groups within this population, and therefore evidence for the design and implementation of targeted screening and coping strategies.. Finally, this study highlights the association between depressive like symptoms and the number and severity of stressful life events, underscoring the necessity of interventions not only at an individual level, but also at the community level.
Keywords: Students; University; Depressive Symptoms; Substance Use; Stressful Life Events; Psychiatric Disorders; Φοιτητές; Πανεπιστήμιο; Συμπτώματα Κατάθλιψης; Χρήση Ουσιών; Ψυχικές Διαταραχές